ANALYSIS OF SALARY AND INCENTIVES ON LECTURERS' PERFORMANCE AT AL AZHAR UNIVERSITY MEDAN - Saidan Sany Lubis (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2025)
This study aims to analyze the effect of salary and incentives on lecturer performance at Al Azhar University Medan. Lecturer performance is a major factor in improving the quality of education, which is influenced by various aspects, including financial compensation. This study uses a quantitative method with regression analysis techniques. The results of the study indicate that salary and incentives have a positive and significant effect on lecturer performance, both partially and simultaneously. This finding confirms that good compensation can increase lecturer motivation, productivity, and loyalty in carrying out their academic duties. Therefore, salary and incentive policies must be adjusted to the needs and expectations of lecturers in order to achieve optimal performance.